SIGNIFICANCE OF BACTERIA IN NATURAL AND EXPERIMENTAL SEDIMENTATION OF CARBONATES, PHOSPHATES, AND SILICATES - Ushatinskaya G.T.; Zhegallo E.A.; Gerasimenko L.M.; Zaitseva L.V.; Orleanskii V.K. (My University, 2006)
The role of bacteria in sedimentation of phosphorites, siliceous and carbonate rocks is discussed. Preservation of bacterial bodies in fossil condition, even in very ancient deposits, is connected with their very early mineralization. A series of laboratory experiments allowed conditions to be reproduced that could have led to mineralization of cyanobacteria and their preservation in sedimentary deposits. The experiments have also shown the important role of cyanobacteria and their metabolic products in the formation of some carbonate minerals, as well as in the accumulation of stromatolites. © Pleiades Publishing, Inc. 2006.
Keywords: BACTERIAL PALEONTOLOGY; CYANOBACTERIA; EXPERIMENTAL GEOMICROBIOLOGY; STROMATOLITES